Mathematics in Art: Color Symmetries of Pampanga’s Giant Christmas Lanterns - Evidente, Imogene F.; Carreon, Angela D. (LIRIP Journal of Interdisciplinary Studies; Vol 3 (2020): LIRIP Journal of Interdisciplinary Studies, 2021)
One of the marks of Kapampangan art and culture is the Giant Christmas Lantern. Every Christmas season, giant lanterns designed by Pampanga's artists are displayed during the Giant Lantern Festival, known locally as "Ligligan Parul". In the Kapampangan vernacular, "parul" and "ligligan" mean lantern and competition respectively. In essence, the term "Ligligan Parul," embodies the contest among different barangays of creating the best giant lantern in the province. The colorful and symmetric designs of these giant lanterns have an entrancing effect and have become more and more intricate through the years. This contribution explores the giant lantern as math art. The underlying uncolored designs of giant lanterns are simple symmetrical patterns whose mathematical structures are well known. There are various mathematical methods for coming up with the symmetric colorings of such patterns. We investigate the color symmetry of existing giant parol designs by matching them with color symmetry algorithms that make use of the subgroup structure of the symmetry group of a pattern. Finally, we demonstrate how to obtain symmetric colorings of the giant lantern that do not match any of the existing designs.